MINING EXTRACTION PRATICES IN THE NEOLIBERAL ERA: SHARIA ECONOMIC PERSPECTIVE ON NATURAL RESOURCE EXPLOITATION AND DAMAGE TO SOCIAL ORDER - Samsuddin; Hedi Firmansyah (Assets Journal: Journal of Economic and Business, 2025)
The expansion of mining activities in Indonesia has intensified under the neoliberal economic paradigm, which emphasizes market liberalization, investment facilitation, and the commodification of natural resources. While this model has contributed to economic growth, it has also generated various ecological and social problems, including environmental degradation, agrarian conflicts, inequality in resource distribution, and the marginalization of local communities. This study aims to analyze mining extraction practices in the neoliberal era from the perspective of Sharia economics and to formulate an alternative model of natural resource governance based on Islamic principles. This research employs a qualitative method with a library research approach. Data were collected from primary sources, including the Qur’an, Hadith, and classical and contemporary Islamic economic literature, as well as secondary sources such as mining regulations, academic journals, books, and reports from relevant institutions. The collected data were analyzed using qualitative content analysis and a descriptive-critical approach. The findings indicate that neoliberal mining governance in Indonesia is characterized by regulatory liberalization, the increasing involvement of private corporations, and the concentration of economic benefits among state and corporate actors. From the perspective of Sharia economics, such practices contradict the principles of al-'adl (justice), maslahah (public welfare), milk al-ummah (public ownership), and maqashid al-shariah. Furthermore, mining extraction has caused ecological damage and social inequality, thereby undermining the objectives of protecting life, wealth, future generations, and the environment. This study argues that an ideal mining governance model should prioritize public ownership, environmental sustainability, equitable distribution of benefits, and community participation through the principle of shura. Therefore, Sharia economics offers an alternative paradigm that positions natural resources as a collective trust (amanah) to be managed for social justice, ecological sustainability, and the welfare of present and future generations.